Potret Mushaf Kontemporer di Indonesia - Imam Arif Purnawan (SUHUF, 2020)
The Indonesian Standard Mushaf is the reference mushaf for all the publisher in Indonesia. Since determination of the Indonesian Standard Mushaf in 1984, model and presentation of the mushaf in Indonesia experienced the transformation from time to time. There are many variants of the model of the cover design presented from year to year by giving arise to new innovation. The publisher of the Qur’an keep on innovating the modification of the cover and the model of presentation of the mushaf by adjusting the trend that people like. This writing tries to explain the extent to which these changes occur and what factor influence in the presentation model of the mushaf. The result of the study shows that the changes occurred significantly in the early year of 2000s. The changes can be observed in the model of the calligraphic writing, cover design and the supplement of the text content. Some driving factors of the changes is the development of technology and the trend of reading the holy Qur’an which was increased in the middle level of muslim society. On the other hand, in the case of model presentation design of the mushaf, local culture turns out to have a strong and significant impact.